A participação das instituições de educaçao superior confessionais na história da educação brasileira - Oliveira, átila Brandão de (2011)
The research aims to present the Christian Confessional Organizations as spaces of extreme importance for the construction of Brazilian education s history. To understand the role of these organizations and their influence, we broach about the installation of the Protestant Christian institutions in Brazil, since educational philosophies resulting from the modernity were deployed in the country through the missions established at schools with such pedagogical innovations. The study also examines the contradictions of the transition from the Middle Ages to the Modern Age, whereat education linked to the religious spaces was vehemently criticized. It was the philosophical attempt to withdraw from society the influence of religion, seeking to build a society ruled by reason and scientism. However, understanding the role of confessional education needs a comprehension of the Middle Ages, in an attempt to understand the quarrels with the Reformed position. This period mark the begin of the a faith-based education committed to training people regardless of their social classes begins to emerge. Finally, the job discusses the role of confessional superior education today in an attempt to understand if it is still effective today in the education field within Brazilian society and how Brazilian Baptist University, a faith-based HEI, externalizes its confessional activity in Salvador s society.